Implementation of Community Service Activities by PT Adi Sarana Armada Tbk as a Corporate Social Responsibility Program for Community Welfare - Bayu Priambodo; Amelia Diva Effendy (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2023)
Problems regarding the environment, natural disasters, poverty, ignorance, infectious diseases, accessibility to life and clean water are the impacts of various company activities. Those who experience these problems are individuals, society, and all aspects of life. The existence of Corporate Social Responsibility (CSR) is a form of corporate social responsibility for the welfare of society. PT Adi Sarana Armada Tbk (ASSA) is a company that provides vehicle rental services for corporations, logistics transportation, and driver services. ASSA has implemented CSR programs since 2012. The categories of CSR activities at ASSA are divided into three, namely education, health, and community social activities. Various programs have been implemented to help the community, government, and the world in dealing with social and environmental problems. This activity has a positive impact on improving people's welfare.